Firstborn of Venice Vicenza in the Early Renaissance State - Grubb, James S. (Johns Hopkins University Press, 2019)
Selected by Choice Magazine as an Outstanding Academic TitleOriginally published in 1988. In the decades after 1404, traditionally maritime Venice extended its control over much of northern Italy. Citizens of Vicenza, the first city to come under Venetian rule, proclaimed their city "firstborn of Venice" and a model for the Venetian Republic's dominions on the terraferma. In Firstborn of Venice James Grubb tests commonplace attributes of the Renaissance state through a rich case study of society and politics in fifteenth-century Vicenza. Looking at relations between Venetian and local governments and at the location of power in Vicentine society, Grubb reveals the structural limitations of Venetian authority and the mechanisms by which local patricians deflected the claims of the capital. Firstborn of Venice explores issues that are political in the broadest sense: legal institutions and administrative practices, fiscal politics, the consolidation of elites, ecclesiastical management, and the contrasting governing ideologies of ruler and subjects.